Tinjauan Yuridis Tanggung Jawab Orang Tua terhadap Anak Pasca Perceraian - Muzakki, Muh Afif; Sodiqin, Ali; Qudussalam, Abdul; Murniati, Dewi (JURNAL LEGISIA, 2024)
Divorce cases in Indonesia are increasing, this has also resulted in many male parents (fathers) ignoring their responsibilities to their children. In connection with legal provisions, children must still receive their rights as children based on Article 45 paragraph 1 of Law no. 1 of 1974 concerning Marriage which states "Both parents are obliged to care for and educate their children as best as possible". The aim of this research is to analyze and identify parents' responsibilities towards children after divorce, as well as legal efforts that can be taken to guarantee children's rights. This research uses normative legal research methods, with a statutory regulation approach and secondary data as research references. The research results show that parents' responsibilities towards children after divorce include the responsibility to meet the child's living needs, provide emotional support, and provide adequate education and teaching. Legal efforts that can be taken to guarantee children's rights include efforts to settle outside of court and submitting a petition to court. In this case, the court can decide on matters relating to children's rights, such as custody, maintenance and the interests of the child as a whole. This research provides a more comprehensive view of the legal issues relating to parental responsibility after divorce. In addition, this research can provide insight to the public on the importance of safeguarding children's rights and welfare in the context of divorce, while encouraging awareness of the responsibility of parents in providing the necessary protection and support for the optimal development of their children.